Hypoeutectic Al-Si Alloy with Cr, V and Mo to Pressure Die Casting - Szymczak T.; Gumienny G.; Stasiak I.; Pacyniak T. (Archives of Foundry Engineering, 2017)
This paper presents the results of hypoeutectic 226 grade alloy as well as prepared on its basis Al-Si alloy containing Cr, V and Mo. The additives tested were added as AlCr15, AlV10 and AlMo8 master alloys. Alloys tested were poured into DTA sampler as well as using pressure die casting. An amount of Cr, V and Mo additives in alloy poured into DTA sampler comprised within the range approximately 0.05-0.35%. Alloys to pressure die casting contained 0.05-0.20% Cr, V and Mo. The crystallization process was examined using the derivative thermal analysis (DTA). The microstructure of castings made in the DTA sampler as well as castings made with use of pressure die casting were examined. The basic mechanical properties of castings made using pressure die casting were defined too. It has been shown in the DTA curves of Al-Si alloy containing approximately 0.30 and 0.35% Cr, Mo, and V there is an additional thermal effect probably caused by a peritectic crystallization of intermetallic phases containing the aforementioned additives. These phases have a morphology similar to the walled and a relatively large size. The analogous phases also occur in pressure die casting alloys containing 0.10% or more additions of Cr, V and Mo. The appearance of these phases in pressure die casting Al-Si alloys coincides with a decrease in the value of the tensile strength Rm and the elongation A. It has been shown die castings made of Al-Si alloys containing the aforementioned additives have a higher Rm and A than 226 alloy.